Application of ICT in the processes of design and construction of an Orthodox Church - Gimenez-Mateu, Luis; Navarro-Delgado, Isidro; Santana-Roma, Galdric (Revista de la Construcción. Journal of Construction, 2016)
This paper presents a study on the implementation of ICT (Information and Communication Technologies) in the architectural project for the new temple that the Romanian Orthodox Church builds in Barcelona (Catalonia). Initially, the reader is introduced to the special circumstances that made this project unique, given the formal complexity that had to be accommodated. In the subsequent sections, different technological tools used for the 3D representation of the building are analyzed. This is necessary for the evaluation of the project outcomes. Moreover, this approach ensured that the architectural project met the client’s approval. After this, we comment on the structural peculiarities and construction limitations to which the project had to conform while retaining its maximum expression. Moreover, we reflect on the use of ICT in the process of execution of the work, allowing the reader to appreciate its quality. The objective of the article is to assess whether the procedures and devices tested in scientific research are applicable in practice, and to what extent. This analysis is performed from the point of view of the project architect, the user/customer and the contractor responsible for running the construction site.